2022
DOI: 10.4103/jfmpc.jfmpc_263_22
|View full text |Cite
|
Sign up to set email alerts
|

A case series of malignant pericardial effusion

Abstract: The most common primary malignancies that affect the pericardium are lung cancers. Typically, pericardial involvement stays undiagnosed, with almost 1-20% of all tumor-related autopsies revealing invasion of the pericardium. Pericardial effusions are seldom the first location of metastasis and presentation of a primary malignancy. Malignant pericardial effusions are usually silent, although they cause dyspnea, chest discomfort, arrhythmias, cough, and, in rare cases, pericardial tamponade. In a patient with ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The fact that nurses did not have enough information about the treatment of a symptom that affects life may affect the results of care. [16][17][18][19] Palliative surgical procedures accounts for a large percentage of surgical procedures performed and constitute 10-20% of all surgical procedures performed in oncology practice. 4,20 It was found that most of the nurses had no idea about this issue and had the wrong information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that nurses did not have enough information about the treatment of a symptom that affects life may affect the results of care. [16][17][18][19] Palliative surgical procedures accounts for a large percentage of surgical procedures performed and constitute 10-20% of all surgical procedures performed in oncology practice. 4,20 It was found that most of the nurses had no idea about this issue and had the wrong information.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that nurses did not have enough information about the treatment of a symptom that affects life may affect the results of care. 1619…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusions are described as the accumulation of fluid within the pericardial sac, separating the visceral and parietal layers of the heart [ 1 , 2 ]. The pericardial sac or cavity normally contains 50-100 mL of fluid.…”
Section: Introductionmentioning
confidence: 99%
“…This cavity can accommodate over 1000 mL without cardiac compromise when accumulated slowly [ 3 ]. Major causes of pericardial effusion include infection, malignancy, heart failure, renal failure, liver cirrhosis, autoimmune disease, Dressler syndrome, and medications such as hydralazine and procainamide [ 1 ]. Primary pericardial neoplasms are 40x less common than metastatic pericardial effusions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation